Loyalty Level of Traditional Retail Stores to Suppliers in the Era of Digital Transformation in Indonesia - Mujianto; Hartoyo; Rita Nurmalina; Eva Z. Yusuf (Bina Nusantara University, 2023)
In Indonesia, the loyalty of traditional retail stores to suppliers in business relationships has not been widely described and explored, especially in the current era of digital transformation. Meanwhile, their business potential is enormous, with an estimated business value of 817 trillion per year. This business value contributes to 69% of the total Fast Moving Consumer Goods (FMCG) retail industry business in Indonesia. The research aimed to describe the situation of traditional retail stores with suppliers and their level of loyalty in the Business to Business (B2B) market. The research also wanted to find out the respondents’ profiles in relation to loyalty indicators. The method applied was a descriptive analysis method to map perceptions and opinions of traditional retail stalls against suppliers. Furthermore, the Top Two Box method was used to assess the loyalty level, while the respondents’ profiles were analyzed using cross-tabulation analysis. The respondents were 500 owners of traditional retail stores with proportionate stratified random sampling through an offline questionnaire. The results show that the retail service quality, trust, commitment, and satisfaction are relatively good. Meanwhile, the merchandising and website quality need to be improved. Approximately 75,4% of retail stores are loyal to their suppliers, while the remaining 24,6% are disloyal. These results are useful for supply companies to establish business-to-business relationships with traditional retail stores in Indonesia to create, develop, and maintain maximum loyalty.